Parental understanding of our communication of morbidity associated with paediatric cardiac surgery: a qualitative study - Katherine Brown; Veena Rajagopal (BMJ Publishing Group, 2020)
Background Following paediatric cardiac surgery, quality of life may be significantly impacted by morbidities associated with cardiac surgery. Parental understanding of the potential for postoperative morbidity is important for informed decision making. As part of a broader research study, we aimed to elicit parental understanding and experience of the communication of morbidities following their child's cardiac surgery, using traditional focus groups together with an online forum.Methods The Children's Heart Federation set up and moderated a closed, anonymous online discussion group via their Facebook page, focusing on complications, information needs and methods of providing families with information. Additionally, we ran three focus groups with parents/carers, moderated by an experienced independent professional. Focus groups were recorded and transcribed and a single transcript was generated from the online forum. All transcripts were thematically analysed.Results All data were collected in 2014. The forum ran over 3 months in 2014 and involved 72 participants. Focus groups involved 13 participants. Three broad themes were identified: (1) clinicians' use of language, (2) feeling unprepared for complications and (3) information needs of families.Conclusions Clinicians' language is often misunderstood, with wide variability in the way morbidities are described, and between differing teams looking after the same child. Information may not be easily absorbed or retained by families, who often felt unprepared for morbidities that arose after their child's heart surgery. Here, we propose key principles of good communication tailored to the individual receiving it.